Beyond the Paycheck: Unveiling the Combined Effect of Skill and Reward on Employee Motivation and Effectiveness - Mutmainah, Mutmainah (Dinasti International Journal of Management Science, 2024)
The purpose of this study was to determine the effect of competence and compensation on employee performance, both simultaneously and partially, and discussed descriptively. The research method used is descriptive and verification. The unit of analysis in this study is the employees of PT. XYZ Branch taken as many as 47 samples (n). The findings of this study are employee competencies are generally assessed on good criteria; Compensation provided to employees is inadequate; employee performance has a fairly high performance and Compensation and competence together or individually affect the performance of employees of PT. XYZ Branch. But partially dominant compensation affects employee performance rather than competence.